Aggregated Risk Assessment and Survey for Risk Reduction in Oil Terminals - Robertas Alzbutas (MDPI AG, 2021)
One of the goals of any oil terminal is to make a business while avoiding hazardous events and harmful effects for both humans and the environment. This can be achieved by creating a safe working place as well as by performing safe and acceptable activities regarding the impact on surrounding objects, including residential and industrial areas. The aim of the hazard analysis of the oil terminal is to assess the risks related to hazardous events or phenomena and to evaluate whether the assessed risks are acceptable. The hazard analysis and assessment of risk are also used for risk reduction while examining and limiting hazardous scenarios that, for instance, involve the loss-of-containment of flammable or combustible material. In this paper, the authors aim to contribute to risk research by providing a comprehensive methodology of risk assessment for oil terminals with case study results and discussion on features of the methodology, risk aggregation, its applicability for risk reduction, and industrial interests. The performed study considered the “Klaipedos Nafta AB” (an operator of the Klaipeda Oil Terminal, Lithuania) case study regarding hazardous materials that might be released from various tanks, devices, and associated pipelines. The performed quantitative risk assessment has enabled the determination of the probability regarding whether releases would ignite and, for instance, cause explosion. In the case study, the estimate of probability, i.e., the frequency, and the possible consequences of the hazardous events were evaluated, and both mitigation and risk reduction measures were also considered.